2019
DOI: 10.2478/rtuect-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Polymer Matrix Composite Waste Recycling Methods

Abstract: Polymer-based matrix composite materials are in high demand in many different fields: aeronautics, pressure vessel manufacturing, wind turbine blade manufacturing, and others. Due to the great mechanical properties of fiber reinforced plastics, it is a desirable material for various applications, but at the same time its heterogenic structure makes the composite waste hard to recycle. This paper focuses on different fiber reinforced plastics (FRP) waste recycling methods and their comparison by carrying out li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 37 publications
0
29
0
1
Order By: Relevance
“…The Technique for Order Preference by Similarity to Ideal Solution (TOPSI S) methodology was the chosen one as multi-criteria analysis system for selecting the path to follow in the energy sector. This method concept relies on the chosen alternative that should have the shortest distance from the ideal solution and the farthest from the negative-ideal solution and it has been used before for selecting application methods within the environmental field [32], [33].…”
Section: Multi-criteria Analysismentioning
confidence: 99%
“…The Technique for Order Preference by Similarity to Ideal Solution (TOPSI S) methodology was the chosen one as multi-criteria analysis system for selecting the path to follow in the energy sector. This method concept relies on the chosen alternative that should have the shortest distance from the ideal solution and the farthest from the negative-ideal solution and it has been used before for selecting application methods within the environmental field [32], [33].…”
Section: Multi-criteria Analysismentioning
confidence: 99%
“…Group of authors [20] showed eight sustainability performance criteria chosen for carrying out multicriteria decision making analysis (MCDA) to compare four alternative polymer matrix composite waste recycling methods. From this last study [21], it can be seen the complexity of choosing an optimal recycling method for a particular composite material of interest.…”
Section: Fluidized Bed Recycling Processmentioning
confidence: 99%
“…There are several multiple criteria decision analysis (MCDA) methods to combine sustainability metrics. The effectiveness of MCDA for complex assessments has been established in the literature (Zanakis et al, 1998;Pohekar and Ramachandran, 2004;Chen et al, 2013;Jayaraman et al, 2015;Delvere et al, 2019;Sassanelli et al, 2019). Amongst the MCDA methods, Analytical Hierarchy Process (AHP) is the most frequently used method (Pohekar and Ramachandran, 2004;Liu et al, 2011;Diamond et al, 2014).…”
Section: Introductionmentioning
confidence: 99%